2010
DOI: 10.1111/j.1440-1827.2010.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured mucinous cystic neoplasm with an associated invasive carcinoma of pancreatic head in a pregnant woman: Report of a case and review of literature

Abstract: Mucinous cystic neoplasm (MCN) of the pancreas is characterized by mucin-producing columnar epithelium and an ovarian-type stroma. It occurs almost exclusively in women and is almost always located in the pancreatic body or tail. Here, we report a case of large MCN located in the pancreatic head but not in the body nor tail in a 32-year-old pregnant woman, which was thought to have grown rapidly during pregnancy. It was ruptured at 34 weeks of gestation and the patient was admitted to the emergency department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
0
40
0
2
Order By: Relevance
“…In the English literature there are only two reports of patients who delivered vaginally at term [4,5], and in 1 case the tumor was discovered only 2 months after delivery [5]. Of the other 8 PMCNs reported, 7 were resected during the second trimester of pregnancy [6,7,8,9,10,11,12] and one at 34 weeks (due to cyst rupture [13]). In the majority of these cases, the diagnosis of PMCN was incidental during routine ultrasound evaluation in the first two trimesters of gestation, the tumors being completely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the English literature there are only two reports of patients who delivered vaginally at term [4,5], and in 1 case the tumor was discovered only 2 months after delivery [5]. Of the other 8 PMCNs reported, 7 were resected during the second trimester of pregnancy [6,7,8,9,10,11,12] and one at 34 weeks (due to cyst rupture [13]). In the majority of these cases, the diagnosis of PMCN was incidental during routine ultrasound evaluation in the first two trimesters of gestation, the tumors being completely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Naganuma et al [13] report a PMCN ruptured at 34 weeks of pregnancy, which probably grew during pregnancy (the event imposed an emergency caesarian section, followed immediately by a pancreaticoduodenectomy). Immunohistochemistry showed only a partial immunopositivity for progesterone receptors and a strong one for α-inhibin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In review of literature we found only five cases of spontaneous rupture of cysadenoma of pancreas. [10][11][12][13][14][15] Naganuma et al 10 reported ruptured mucinous cystic neoplasm with associated invasive carcinoma of pancreatic head in a pregnant woman. Heim et al 11 reported ruptured cystadenoma of the pancreas in a 85-year-old woman.…”
Section: Discussionmentioning
confidence: 99%